Effect of Oxygen Pressure on Thermoelectric Properties of p-Type CuAlO2 Films Fabricated by Pulsed Laser Deposition - Saini, Shrikant; Mele, Paolo; Osugi, Shunsuke; Adam, Malik Ismail (Springer Verlag (Germany), 2018)
We focus on the growth of p-type CuAlO2 thin films and its thermoelectric properties. Thin films are deposited by pulsed laser deposition technique on single-crystal sapphire substrates varying the oxygen partial pressure. Thin film deposited at oxygen partial pressure of 200 mTorr presents bigger grains (about 10 μm in size) and shows Seebeck coefficient as high as 270 µV/K with a conductivity of about 0.8 S/cm so that its power factor is about 5.7 µW/mK2 at 800 K, twice than observed in the film deposited at 60 mTorr of oxygen.